La Marionetta e il burattino. Due presentazioni - Vari, Autori (Il sogno della farfalla, 2011)
We are publishing the talks and the debates that followed at two book launches of La marionetta e il burattino, Massimo Fagioli’s second book, first published in 1974, and now released under the Asino d’oro label containing a new preface. The launches were held in a Roman book shop and at the Salone internazionale del libro di Torino (Torino book fair), respectively in April and May 2011, and explored the main themes of the book, from the definition of psychopathology to the research on the male-female relationship, the language featured in the book, and its multifaceted meanings: its meaning in relation to the previous volume of the author, Istinto di morte e conoscenza (Death drive and knowledge); its relevance in paving the way, soon after its publication, for the setting up of the Collective Analysis; the crucial role it plays, both then and now, in the training of psychiatrists and psychotherapists who follow Fagioli’s theory and the praxis of the Collective Analysis.